UVB-Induced Oxidative Collapse and Melanogenic Activation in a Rat Model of Cutaneous Hyperpigmentation: A Multi-Parametric Analysis - Sesia Pradestine; Endra Yustin Ellistasari; Nurrachmat Mulianto; Indah Julianto; Muhammad Eko Irawanto; Nugrohoaji Dharmawan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Ultraviolet B (UVB) radiation is a primary driver of cutaneous hyperpigmentation disorders, with oxidative stress recognized as a key pathogenic mechanism. However, a comprehensive, multi-level characterization of the causal link between chronic UVB exposure and the resulting oxidative, histological, and melanogenic responses is needed. This study aimed to quantitatively validate a preclinical model of UVB-induced hyperpigmentation by characterizing the reciprocal regulation of key oxidative stress biomarkers and correlating these changes with objective histological evidence of hyperpigmentation. Methods: This controlled in vivo experimental study used 14 male Sprague Dawley rats, divided into a control group (KN; n=7) and a UVB-exposed group (KP; n=7). The KP group received chronic UVB radiation (300 mJ/cm² daily, 5 days/week for 4 weeks). Dorsal skin tissue was harvested for analysis. Oxidative stress was assessed by quantifying malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) levels via ELISA. Hyperpigmentation was objectively validated and quantified using Fontana-Masson staining for melanin deposition and immunohistochemistry for microphthalmia-associated transcription factor (MITF). Results: Chronic UVB exposure induced significant hyperpigmentation, confirmed by a 5.8-fold increase in epidermal melanin content (p < 0.001) and a 4.1-fold increase in the number of MITF-positive melanocytes (p < 0.001) in the KP group. This was accompanied by a profound oxidative imbalance: MDA levels increased by 7.5-fold (p < 0.001), while the activities of SOD, CAT, and GPx decreased by 80.5%, 65.2%, and 71.4%, respectively (all p < 0.001). A strong negative correlation was observed between MDA and all antioxidant enzymes, particularly SOD (r = -0.985, p < 0.001). Conclusion: Chronic UVB exposure directly triggers a collapse of the cutaneous antioxidant network, leading to severe lipid peroxidation. This state of profound oxidative stress is causally linked to melanocyte activation and excessive melanin synthesis, driving the hyperpigmentation phenotype. This robustly validated preclinical model provides a powerful platform for investigating the molecular pathophysiology of UVB-induced pigmentary disorders and for evaluating novel therapeutic interventions.